Visual effects of a forward-curled 3D map of the Forbidden City with eye-tracking - Shen Ying; Junru Su; Yuan Zhuang; Lina Huang (Geo-spatial Information Science)
In urban environment visualization, including both traditional two-dimensional (2D) and three-dimensional (3D) visualization, the height of ground objects results in visual occlusions in ordinary 3D maps, which leads to challenges in displaying spatial relationships. We empirically studied the visual effects of a curled deformation method and assessed whether curled deformation visualization could help participants complete wayfinding tasks. The results revealed that a forward-curled map can include both ego-view and bird-view perspectives, ensure continuity from ego-view to bird-view perspectives, and address foreshortening effects. The remote, distant areas are pulled closer, thereby enhancing the sense of space and allowing participants to better understand the overall situation. A forward-curled map has a wider coverage range of fixation points and a wider scope of visual search and can improve a participant’s task completion efficiency. Moreover, the cognitive burden is not increased with this approach.